Inequality in developing countries: levels and recent trends - Gasparini, Leonardo Carlos (2013)
This paper reviews the empirical evidence on the levels and trends in income/consumption inequality in developing countries. It includes a discussion of data sources and measurement issues, evidence on the levels of inequality across countries and regions, an assessment of trends in these variables since the early 1980s, and a general discussion of their determinants. The available evidence suggests that on average the levels of national income inequality in the developing world increased in the 1980s and 1990s, and declined in the 2000s.